Reducing passive drug diffusion from electrophoretic drug delivery devices through co-ion engineering - Chen, S-T; Renny, MN; C. Tomé, L; Olmedo-Martínez, JL; Udabe, E; Jenkins, EPW; Mecerreyes, D; Malliaras, GG; McLeod, RR; Proctor, CM (Wiley, 2021)
Implantable electrophoretic drug delivery devices have shown promise for applications ranging from treating pathologies such as epilepsy and cancer to regulating plant physiology. Upon applying a voltage, the devices electrophoretically transport charged drug molecules across an ion-conducting membrane out to the local implanted area. This solvent-flow-free “dry” delivery enables controlled drug release with minimal pressure increase at the outlet. However, a major challenge these devices face is limiting drug leakage in their idle state. Here, a method of reducing passive drug leakage through the choice of the drug co-ion is presented. By switching acetylcholine's associated co-ion from chloride to carboxylate co-ions as well as sulfopropyl acrylate-based polyanions, steady-state drug leakage rate is reduced up to sevenfold with minimal effect on the active drug delivery rate. Numerical simulations further illustrate the potential of this method and offer guidance for new material systems to suppress passive drug leakage in electrophoretic drug delivery devices.